2021
DOI: 10.3390/polym13071149
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Metakaolin-Based Geopolymer with Cathode Ray Tube Glass

Abstract: Geopolymers can be treated as an environmentally friendly alternative for concrete and enables utilization of various wastes. This paper focuses on the possibility of application of discarded cathode ray tube (CRT) glass inside a metakaolin-based geopolymer in the form of an aggregate, providing an ecological method of recycling of this hazardous material. The main goal of this paper was to develop an optimal composition of a new geopolymer and to describe its behavior under varying curing conditions. A geopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…On the other hand, if gases can be released from the raw materials through the voids between particles in a larger fraction, they do not affect the mechanical strength as much as when they destroy the compactness of the material, leaving it with lower density and lower compressive and bending strength. The density of the FA was 2.288 ± 0.001 g cm −3 , whereas the MK density of 2.566 ± 0.001 g cm −3 was compliant with the specifications presented by the manufacturer (2.50- The density of the FA was 2.288 ± 0.001 g cm −3 , whereas the MK density of 2.566 ± 0.001 g cm −3 was compliant with the specifications presented by the manufacturer (2.50-2.80 g cm −3 ) and other authors [82,83].…”
Section: Resultssupporting
confidence: 69%
“…On the other hand, if gases can be released from the raw materials through the voids between particles in a larger fraction, they do not affect the mechanical strength as much as when they destroy the compactness of the material, leaving it with lower density and lower compressive and bending strength. The density of the FA was 2.288 ± 0.001 g cm −3 , whereas the MK density of 2.566 ± 0.001 g cm −3 was compliant with the specifications presented by the manufacturer (2.50- The density of the FA was 2.288 ± 0.001 g cm −3 , whereas the MK density of 2.566 ± 0.001 g cm −3 was compliant with the specifications presented by the manufacturer (2.50-2.80 g cm −3 ) and other authors [82,83].…”
Section: Resultssupporting
confidence: 69%
“…On the other hand, we are assisting an increasing interest in room consolidated materials obtained by the alkali activation of aluminosilicate powders, also known as geopolymers, which are suitable for the incorporation of quite a lot of various wastes produced from different sources [ 14 , 15 , 16 ], among which wastes of glasses is just one. As reported by the review paper by Luhar et al [ 17 ], the process of geopolymerization is capable of producing various inorganic binders containing waste glass which are suitable for different applications (mortars, pre-cast, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…During the manufacturing of GPC, the activation process results in increased energy consumption and the production of greenhouse gases that present a safety risk. In addition, the fabrication of GPC is significantly influenced by the curing temperature and duration [ 33 , 34 ]. Saranya et al [ 35 ] explored the behavior of steel fiber-reinforced dolomite-GGBS GPC short compressive members subjected to axial compressive loading and found that these compressive members portrayed higher axial compressive strength than steel fiber-reinforced OPC compressive members.…”
Section: Introductionmentioning
confidence: 99%